2005
DOI: 10.1007/s11141-005-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Drift of Electrons and Atoms in the Laser Radiation Field and Its Influence on the Optical Properties of Semiconductors

Abstract: We experimentally study the influence of the laser-induced drift (LID) of dopant electrons and atoms on the optical properties of semiconductors. It is shown that the LID of electrons results in a dramatic change in the refractive index in the region of laser-radiation output from semiconductor crystals, impairement of the total internal reflection in semiconductors, and the occurrence of astigmatism during self-defocusing of the laser radiation in anisotropic semiconductors. This effect influences the breakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The laser-induced drift of electrons changes the threshold damage of the output surface of the semiconducting crystals. 3 Such a drift of electrons in the radiation field must also be observed in metals. This effect is usually weak in massive metals because of their high electron concentration and large absorption factor.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The laser-induced drift of electrons changes the threshold damage of the output surface of the semiconducting crystals. 3 Such a drift of electrons in the radiation field must also be observed in metals. This effect is usually weak in massive metals because of their high electron concentration and large absorption factor.…”
Section: Introductionmentioning
confidence: 96%
“…However, for hybrid multilayer film nanostructures, such a laser impact can cause essential changes in their magneto-optical properties. 3 In the presented paper, we have studied the interaction of the laser radiation with hybrid multilayer films containing thin magnetic and nonmagnetic layers. It is shown that the laser-induced drift of spin-polarized conducting electrons from the ferromagnetic layer results in nonequilibrium magnetization in the nonmagnetic layer.…”
Section: Introductionmentioning
confidence: 99%